Workshop Pembelajaran Bahasa Inggris Berbasis Teknologi AI Untuk Guru SD Swasta Islami Annur Air Joman Baru - Maulana, Cecep; Irianto, Irianto; Amin, Muhammad Amin; Wirjaya, Salsabila (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
This workshop aimed to enhance teachers' competencies in integrating Artificial Intelligence (AI) technology into English language teaching practices. It began with a needs assessment survey to identify the challenges teachers face in utilizing technology. The implementation methods included interactive training sessions, demonstrations of AI-based applications such as learning chatbots, and hands-on support in designing technology-based lesson plans.The workshop results showed that the pre-test score totaled 1,795, with an average score of 59.83. Following the training, a post-test was conducted to measure the improvement in teachers' understanding through the use of the chatbot application. The post-test score reached 2,520, with an average post-test score of 84.00, reflecting an increase of 30 points. This significant improvement highlighted the teachers' enhanced understanding and skills in using AI to create more dynamic, student-centered learning environments. Teachers expressed greater confidence in exploring innovative teaching methods that boost student motivation and participation. It is hoped that this training model can be adapted to other educational settings to support the sustainable integration of technology.Keywords: artificial intelligence; english language learning; primary school teachers; AI technology. Abstrak: Pelatihan ini bertujuan untuk meningkatkan kompetensi guru dalam mengintegrasikan teknologi Artificial Intelligence (AI) ke dalam praktik pengajaran bahasa Inggris. Pelatihan dimulai dengan survei penilaian kebutuhan untuk mengidentifikasi tantangan yang dihadapi guru dalam memanfaatkan teknologi. Metode pelaksanaannya meliputi sesi pelatihan interaktif, demonstrasi aplikasi berbasis AI seperti chatbot pembelajaran, dan pendampingan langsung dalam merancang rencana pembelajaran berbasis teknologi. Hasil lokakarya menunjukkan bahwa skor pre-test mencapai 1.795, dengan skor rata-rata 59,83. Setelah pelatihan, dilakukan post-test untuk mengukur peningkatan pemahaman guru melalui penggunaan aplikasi chatbot. Skor post-test mencapai 2.520, dengan skor rata-rata post-test 84,00, yang mencerminkan peningkatan sebesar 30 poin. Peningkatan yang signifikan ini menyoroti peningkatan pemahaman dan keterampilan guru dalam menggunakan AI untuk menciptakan lingkungan belajar yang lebih dinamis dan berpusat pada siswa, dan para guru menyatakan kepercayaan diri yang lebih besar dalam mengeksplorasi metode pengajaran inovatif yang dapat meningkatkan motivasi dan partisipasi siswa. Diharapkan model pelatihan ini dapat diadaptasi ke lingkungan pendidikan lainnya untuk mendukung integrasi teknologi yang berkelanjutan.Kata kunci: kecerdasan buatan; pembelajaran bahasa inggris; guru sekolah dasar; teknologi AI.